Biomimetic Bottlebrush Polymer Coatings for Fabrication of Ultralow Fouling Surfaces. (5th December 2018) - Xia, Yinqiang; Adibnia, Vahid; Huang, Renliang; Murschel, Frederic; Faivre, Jimmy; Xie, Guojun; Olszewski, Mateusz; De Crescenzo, Gregory; Qi, Wei; He, Zhimin; Su, Rongxin; Matyjaszewski, Krzysztof; et al.
Abstract: Demand for long‐lasting antifouling surfaces has steered the development of accessible, novel, biocompatible and environmentally friendly materials. Inspired by lubricin (LUB), a component of mammalian synovial fluid with excellent antifouling properties, three block polymers offering stability, efficacy, and ease of use were designed. The bottlebrush‐structured polymers adsorbed strongly on silica surfaces in less than 10 minutes by a simple drop casting or online exposure method and were extremely stable in high‐salinity solutions and across a wide pH range. Antifouling properties against proteins and bacteria were evaluated with different techniques and ultralow fouling properties demonstrated. With serum albumin and lysozyme adsorption <0.2 ng cm −2, the polymers were 50 and 25 times more effective than LUB and known ultralow fouling coatings. The antifouling properties were also tested under MPa compression pressures by direct force measurements using surface forces apparatus. The findings suggest that these polymers are among the most robust and efficient antifouling agents currently known.